IN VITRO COMPARISON OF THE ANTIMICROBIAL EFFECTS OF DIFFERENT ROOT CANAL MEDICAMENTS ON ENTEROCOCCUS FAECALIS AND CANDIDA ALBICANS - Burçin Arıcan; Hesna Sazak Öveçoğlu (Cumhuriyet University, 2021)
Objectives: To evaluate the antimicrobial effects of experimental root canal medicaments on Enterococcus faecalis and Candida albicans on day 3 and day 7 using quantitative polymerase chain reaction (Q-PCR) analyses. Materials and Methods: 240 single-rooted, single-canalled human teeth were used. Root canals were shaped mechanically and embedded in acrylic blocks, then sterilized in an autoclave. The samples were divided into two groups and infected with E. faecalis and C. albicans, and then divided into subgroups (n=10); calcium hydroxide (Ca(OH)2), triple paste (TAP), double paste (DP), modified double paste (MDP), lactoferrin (Lf), negative and positive groups. At the end of 3 and 7 days, paper points containing the root canal samples were placed in empty Eppendorf tubes, and DNA was isolated. Real-time Q-PCR was applied and the data were analyzed statistically. Results: The antimicrobial effects of each medicine increased from days 3 to 7. Ca(OH)2 and TAP groups showed the similar eradication rates for E. faecalis and C. albicans on day 3 and 7 (P > 0.05). There was no significant difference between DP, MDP and Lf for the eradication of microorganisms at both experimental days (P > 0.05), except the amount of eradicated E. faecalis by DP at day 7 in which DP caught the similar percentages with TAP and Ca(OH)2 (P < 0.05). Conclusions: Experimental pastes demonstrated antimicrobial efficiancy similar to those used routinely in endodontic clinic. It is promising that lactoferrin which is a very biocompatible material can be used in different combinations as an intracanal medicament.